Short Communication: Chromosome number and karyotype of five native Phalaenopsis spp. orchid from Indonesia - SRI HARTATI; KRISTINA AYU ISNAENI (Society for Indonesian Biodiversity, 2026)
Abstract. Hartati S, Isnaeni KA. 2026. Short Communication: Chromosome number and karyotype of five native Phalaenopsis spp. orchid from Indonesia. Biodiversitas 27 (7): d270703. https://doi.org/10.13057/biodiv/d270703. Cytogenetic information on native Phalaenopsis species from Indonesia remains limited despite their importance in orchid breeding, taxonomy, and genetic conservation. Chromosome number and karyotype analyses provide essential information for understanding genome organization, evolutionary relationships, and species differentiation within the genus. This study aimed to characterize chromosome number and karyotype structure of five native species of Phalaenopsis (P. amabilis, P. amboinensis, P. deliciosa, P. gigantea, and P. violacea) from Indonesia using the aceto-orcein squashing method. Chromosome observations were performed on actively dividing root tip cells at the metaphase stage. The results showed that all examined species possessed the same chromosome number of 2n = 38, indicating a diploid condition with a basic chromosome number of x = 19. Chromosome morphology in all species was metacentric, resulting in a symmetrical karyotype formula of 2n = 2x = 38m. The average total chromosome arm lengths varied among species, ranging from 1.53±0.37 µm in P. gigantea to 2.53±0.61 µm in P. violacea. The Intrachromosomal Asymmetry Index (A1) indicated metacentric chromosome morphology, while the Interchromosomal Asymmetry Index (A2) showed low size variation among chromosomes. These findings provide cytogenetic information useful for taxonomy, breeding programs, and genetic conservation of Phalaenopsis.